The Role of Madrasah Principal and Human Resources Development in Improving the Quality of Madrasah Aliyah at Central Lampung - Sungkowo, Sungkowo; Juhary, Ali (2023)
The purpose of this study was to determine whether there is an influence between the role of the principal of Madrasah Aliyah and the development of Human Resources in improving the quality of Madrasah Aliyah in Central Lampung. The research uses quantitative methods. The results of the first study indicate that there is a significant influence between the role of the principal on the development of Human Resources with a level of influence of 19.62%. Second, there is a significant influence between the development of human resources on improving the quality of Madrasah Aliyah 23.81%. Third, the simultaneous influence of the role of the principal and the development of human resources on improving the quality of Madrasah Aliyah is 45.97%. The remaining 54.03% improvement in the quality of Madrasah Aliyah in Central Lampung Regency is influenced by other factors (role of government, environment, infrastructure, student input and others).